Increasing Inferential Leverage in the Comparative Method: Placebo Tests in Small-n Research. (August 2016) - Glynn, Adam N.; Ichino, Nahomi
We delineate the underlying homogeneity assumption, procedural variants, and implications of the comparative method and distinguish this from Mill's method of difference. We demonstrate that additional units can provide "placebo" tests for the comparative method even if the scope of inference is limited to the two units under comparison. Moreover, such tests may be available even when these units are the most similar pair of units on the control variables with differing values of the independent variable. Small- n analyses using this method should therefore, at a minimum, clearly define the dependent, independent, and control variables so they may be measured for additional units, and specify how the control variables are weighted in defining similarity between units. When these tasks are too difficult, process tracing of a single unit may be a more appropriate method. We illustrate these points with applications to two studies.